Modern perspectives on the gold standard - Bayoumi, Tamim A.; Eichengreen, Barry J.; Taylor, Mark P., 1958- (Cambridge University Press, 1996)
Currency crises in Europe and Mexico during the 1990s provided stark reminders of the importance and the fragility of international financial markets. These experiences led some commentators to conclude that open international capital markets are incompatible with financial stability. But the pre-1914 gold standard is an obvious challenge to the notion that open capital markets are sources of instability. To deepen our understanding of how this system worked, this volume draws together recent research on the gold standard. Theoretical models are used to guide qualitative discussions of historical experience, while econometric methods are used to help the historical data speak clearly. The result is an overview of the gold standard, a survey of the relevant applied research in international macroeconomics, and a demonstration of how the past can help to inform the present.